SOSIALISASI PERAN KADER POSYANDU TERHADAP OPTIMALITAS PELAKSANAAN PELAYANAN KESEHATAN POSYANDU DI KELURAHAN RAWA BUAYA - Dortea Lewen (Jurnal Pengabdian Masyarakat Kesosi, 2020)
Basic health is one indicator to determine the level of community welfare, without community participation, basic health empowerment will not run optimally. Empowerment in the health sector is the process of providing information to individuals, families or groups (clients) continuously and continuously following the client's development, as well as the process of helping clients, so that the client changes from not knowing to knowing or being aware (aspects of knowledge or knowledge), from from knowing to being willing (aspects of attitude or attitude) and from wanting to be able to carry out the introduced behavior (aspects of action or practice). Community empowerment in the health sector is an active process, where the target/client and the empowered community must participate actively (participate) in health activities and programs (MOH, 2006). Community empowerment activities are one of the effective activities in the context of becoming independent and empowering the community. These activities can be done anytime, anywhere and by anyone. Basically, community empowerment activities are shown to the underprivileged community, in order to be able to make them independent, in order to make them able to help themselves. Cadres are the central point in carrying out posyandu activities. It is hoped that their participation and activeness will be able to mobilize community participation. However, the presence of cadres is relatively unstable because participation is voluntary, so it is a guarantee that they will continue to carry out their functions properly as expected. If there are family interests or other interests, the posyandu will be left behind .